1983
DOI: 10.1037/0022-0663.75.3.424
|View full text |Cite
|
Sign up to set email alerts
|

Auditory short-term memory and digit span: Normal versus poor readers.

Abstract: These experiments were conducted to investigate the relationship between reading comprehension level, digit span, and short-term memory for Morse code-like temporal patterns. Consistent with previous research on children, Experiment 1 demonstrated that college students performed better when the first pattern was auditory than when it was visual or tactual. Experiments 2 and 3 found no relationship for either college or fifth-grade students between digit span and accuracy in comparing patterns of tones presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The auditory perceptual problem may extend to nonverbal stimuli in tasks such as indicating the sequence of two stimuli or judging whether two stimuli were presented or only one (Farmer & Klein, 1995; McCroskey & Kidder, 1980; Tallal, 1980). The auditory processing deficit may be reflected in tasks such as the Incomplete Words and Sound Patterns tests used here, or inter- and intramodal matching tasks (Badian, 1977; Hatchette & Evans, 1983; Payne & Holzman, 1983; Zendel & Pihl, 1983). There is some evidence for a deficiency in echoic memory (Hurford & Shedelbower, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The auditory perceptual problem may extend to nonverbal stimuli in tasks such as indicating the sequence of two stimuli or judging whether two stimuli were presented or only one (Farmer & Klein, 1995; McCroskey & Kidder, 1980; Tallal, 1980). The auditory processing deficit may be reflected in tasks such as the Incomplete Words and Sound Patterns tests used here, or inter- and intramodal matching tasks (Badian, 1977; Hatchette & Evans, 1983; Payne & Holzman, 1983; Zendel & Pihl, 1983). There is some evidence for a deficiency in echoic memory (Hurford & Shedelbower, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on children with learning disability, on normal and poor readers, and on adult clinical samples were focused on the processing of only the auditory and visual input modalities. The findings of these studies pointed to the existence of two separate stores for auditory and visual tasks (Curley & Reilly, 1983;Dean & Rothlisberg, 1983;Frick, 1984;Moore, 1986;Payne et al, 1980;Payne & Holzman, 1983;Rothlisberg & Dean, 1985). Although there are data from tests across modalities on clinical samples, there is little information on the effect of modality on digit span in "normal" samples.…”
Section: Figurementioning
confidence: 94%
“…Studies demonstrate the existence of individual preferences and differential difficulty in retaining visual or auditory material and in producing material in spoken or written form (Curley & Reilly, 1983;Dean & Rothlisberg, 1983;Koppitz, 1973;Moore, 1986;Rothlisberg & Dean, 1985). A group of findings demonstrated that normal readers were differentiated from the poor readers when the material was presented in the auditory modality (Payne, Davenport, Domangue, & Soroka, 1980;Payne & Holzman, 1983). Another group of findings showed that task structure, namely, the simultaneous versus sequential presentation of the digits in the VADS Test, could be a basis for differentiating good readers from poor ones (Torgesen, Bowen, & Ivey, 1978).…”
Section: Please Scroll Down For Articlementioning
confidence: 95%
“…Furthermore, one of the most fundamental markers of human intelligence -language learning -depends critically on the ability to learn sequential information and individual differences in both language comprehension and verbal short-term memory are predicted by individual differences in learning sequential transitional probabilities (Misyak & Christiansen, 2012). Unsurprisingly, from this perspective, studies have shown that digit span performance strongly relates to language learning (Gathercole, Hitch, Service, & Martin, 1997;Payne & Holzman, 1983).…”
Section: Digitmentioning
confidence: 96%